Scalloping deformity of the corpus callosum following ventricular shunting. - Numaguchi, Y; Kristt, D A; Joy, C; Robinson, W L (American Journal of Neuroradiology, 1993)
PURPOSE To describe six patients who underwent ventriculoperitoneal (V-P) shunting for hydrocephalus and developed scalloping deformity of the dorsal surface of the corpus callosum, and to evaluate the cause and frequency of this phenomenon.MATERIALS AND METHODS MR images of 35 patients whose hydrocephalus was successfully corrected by V-P shunting were studied. To elucidate the possible anatomic basis for the scalloping deformity, gross examination of the corpus callosum relative to the adjacent anatomical structures was performed using autopsy specimens.RESULTS Of the 35 patients who underwent successful V-P shunting, six (17%) developed a scalloping deformity of the corpus callosum. The deformity was noted exclusively in the body of the corpus callosum. This phenomenon was observed in both obstructive and communicating hydrocephalus regardless of the patient's age, but was particularly noted in patients with tectal tumors.CONCLUSION The cause of this phenomenon may be a combination of long-standing hydrocephalus and normal pericallosal artery anatomy. Prolonged hydrocephalus softens the corpus callosum and the branches of the pericallosal arteries tether the corpus callosum to the overlying cingulate cortex at periodic intervals.